Territoriality and State Succession in Cultural Heritage. Issue 4 (22nd January 2015) - Jakubowski, Andrzej
Abstract: The international legal discourse on the topic of state succession in cultural property has long been dominated by the concept of territoriality—the territorial provenance (origin) of cultural assets. This traditional reasoning was essentially rooted in the idea of the European nation-state. In the last 50 years, the principle of territoriality has also become accommodated within the framework of the preservation of cultural heritage. Yet such territorial and protective approaches do not take into account the value of cultural heritage for society, that is, groups and individuals that have created or maintained a given heritage. This article attempts to explore the potential clash between the principles of territoriality and human rights, with respect to state succession in cultural heritage matters. In this context, it deals with some recent ongoing interstate negotiations on the allocation of and access to cultural property with respect to post–World War II developments in state succession among Poland, Germany, and Ukraine.